Post-traumatic Growth and Related Influencing Factors in Discharged COVID-19 Patients: A Cross-Sectional Study - Yan, Shixin; Yang, Jun; Ye, Man; Chen, Shihao; Xie, Chaoying; Huang, Jin; Liu, Haiyang (Frontiers in Psychology, 2021)
The purpose of this study is to investigate the current state of posttraumatic growth (PTG) and identify its influencing factors in discharged COVID-19 patients. PTG refers to individual experiences of significant positive change arising from the struggle with a major life crisis. This descriptive cross-sectional study used the convenient sampling method to recruit 140 discharged COVID-19 patients in Hunan, China. The results show that the PTG of the discharged COVID-19 patients was positively correlated with self-esteem, posttraumatic stress disorder, coping style tendency, and social support, but negatively correlated with the time from onset to diagnosis. Our findings could provide guidance on improving the psychological state and well-being of discharged COVID-19 patients.